Argentina : Third Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance and Applicability of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
The responsible conduct of macroeconomic policies has continued with the new government. These policies have been key to stabilizing the economic situation and improving growth prospects. Maintaining budgetary control to stimulate the economy and step up social and infrastructure spending is the immediate challenge. The achievement of broad price stability attests to the adept handling of monetary policy. Structural reform implementation remains the major concern. Sustaining the recovery will require the deepening and broadening of structural reforms and the normalization of Argentina's relations with external creditors.